Design and characterisation of a label free evanescent waveguide microscope - Choi, Rebecca (2015)
This project aims to develop and characterise a label-free waveguide microscopy system as an alternative to objective-based total internal reflection microscopy to be applied in the qualitative detection of the adhesion of biological samples. The advantage of the waveguide system allows the use of lower numerical aperture objectives resulting in a larger field of view and a significant cost reduction. A LED illuminated waveguide system was developed in which light is coupled through a conventional microscope slide to produce total internal reflection at the glass-water interface. The evanescent field profile was characterised by displacing a tungsten tip from the glass/water interface and the scattered intensity from the tip was imaged using a low NA objective. A laser illuminated waveguide system was then developed and the microscope slides were modified by polishing the uneven edges, which allowed better control of the incidence angle and the evanescent field was characterised using the same method. To verify that the waveguide signal will only be detected when an objective is proximal to the surface, microspheres under Brownian motion were tracked under bright-field mode and laser waveguide mode. The evanescent field profile was best fitted with a double exponential, however, the evanescent field depth could not be defined due to the presence of an intensity offset of approximately 50% from the normalised intensity. The high intensity offset was reduced to 10% when the edges of the waveguide were polished and a collimated laser source was used. Under laser illumination, for high incident angles, the evanescent field profile showed deviation from the simple exponential function at short separation distances from the substrate. The evanescent field depth based on the best fitted function for incident angles 62.1(deg), 68.1(deg) and 77.4(deg) were 956±55nm, 366±0.6nm and 211±32nm respectively; demonstrating that the evanescent field depth can be controlled by changing the incident angle. Two out of seven tracked microspheres featured a coefficient of variation > 1 over time in the results of the waveguide mode and was not observed in the bright-field mode. The higher coefficient of variation was caused by an intensity spike when the microspheres moved in and out the evanescent field and confirms the validity of the waveguide system. This system can potentially be compatible with standard tissue culture plastics and can be adoptable in an industrial manufacturing setting.